Delivery of a Hepatitis C Virus Vaccine Encoding NS3 Linked to the MHC Class II Chaperone Protein Invariant Chain Using Bacterial Ghosts - Yulang Chi; Shikun Zhang; Shouping Ji (Biomedicines, 2024)
Efficient delivery of a DNA plasmid into antigen-presenting cells (APCs) is a potential strategy to enhance the immune responses of DNA vaccines. The bacterial ghost (BG) is a potent DNA vaccine delivery system that targets APCs. In the present work, we describe a new strategy of using E. coli BGs as carriers for an Ii-linked Hepatitis C Virus (HCV) NS3 DNA vaccine that improved both the transgene expression level and the antigen-presentation level in APCs. BGs were prepared from DH5α cells, characterized via electron microscopy and loaded with the DNA vaccine. The high transfection efficiency mediated using BGs was first evaluated in vitro, and then, the immune protective effect of the BG-Ii-NS3 vaccine was determined in vivo. It was found that the antibody titer in the sera of BG-Ii-NS3-challenged mice was higher than that of Ii-NS3-treated mice, indicating that the BGs enhanced the humoral immune activity of Ii-NS3. The cellular immune protective effect of the BG-Ii-NS3 vaccine was determined using long-term HCV NS3 expression in a mouse model in which luciferase was used as a reporter for HCV NS3 expression. Our results showed that the luciferase activity in BG-Ii-NS3-treated mice was significantly reduced compared with that in Ii-NS3-treated mice. The CTL assay results demonstrated that BG-Ii-NS3 induced a greater NS3-specific T-cell response than did Ii-NS3. In summary, our study demonstrated that BGs enhanced both the humoral and cellular immune response to the Ii-NS3 DNA vaccine and improved its immune protection against HCV infection.